Conditional Cash Transfer Scheme for Protecting the Survival of the Girl Child in Haryana: A Critique. (February 2015) - Gaur, Ruchi; Anand, Sarita
The article explores the issue of the conditional cash transfers scheme for the girl child in Haryana. The beneficiary mothers and the persons involved in the implementation of the scheme were interviewed with the help of an in-depth interview guide to gather quantitative and qualitative data. It was found that though the scheme's aim is to improve attitudes and create a favourable attitude towards the girl child, it has not been able to achieve the desired outcomes. Education and the upbringing of the girl child were not concerns of either parents or stakeholders responsible for implementing the scheme. The questions raised by the study are: when parents still want a male heir for their family, will governmental efforts succeed in stopping female foeticide, especially in the case of a third daughter?